Synthetic Controls with Staggered Adoption - Ben-Michael, Eli,Feller, Avi,Rothstein, Jesse (National Bureau of Economic Research, 2021)
Staggered adoption of policies by different units at different times creates promising opportunities for observational causal inference. Estimation remains challenging, however, and common regression methods can give misleading results. A promising alternative is the synthetic control method (SCM), which finds a weighted average of control units that closely balances the treated unit's pre-treatment outcomes. In this paper, we generalize SCM, originally designed to study a single treated unit, to the staggered adoption setting. We first bound the error for the average effect and show that it depends on both the imbalance for each treated unit separately and the imbalance for the average of the treated units. We then propose
10.3386/w28886
Keywords: Arbeitspapier; Graue Literatur; Kausalanalyse; Regressionsanalyse